The Effect of Cartoon Films on Anxiety Levels in Preschool-Aged Children Undergoing Hospitalization at Hermina Podomoro Hospital - Fitriyati, Fitriyati; Hayyu Naafi Hidhayanti; Ganiyah Mulyani, Ganiyah Mulyani (Journal of Health Empowerment and Interprofessional Practice, 2026)
Background​ study This  based on a number of matter that is  Anxiety in children moment treated at home Sick can influence welfare they , and one of them method For reduce anxiety the is with use technique distractions , such as watching cartoons . Research​ This aim For analyze the influence of cartoon films to level anxiety child age preschool undergoing​ hospitalization at Hermina Podomoro Hospital . The method used in study This is design pre-experiment with one group pretest- posttest design , involving 47 samples child age pre -school care at home sick . Research This done with measure level anxiety child before and after watching cartoons​ as form intervention . Measurement anxiety done with use scale certain . Research results show that the average level anxiety child before intervention is 1.73, which includes in category anxiety moderate , whereas after intervention , average level anxiety down to 1.27, which includes in category anxiety light . Statistical test produces a p-value of 0.004, which indicates significant differences in levels​ anxiety child after watching cartoons . In conclusion , the research This show that cartoon film intervention own influence positive in reduce level anxiety in children age preschool undergoing​ Hospitalization . Visual distraction techniques through cartoon films can become effective alternative​ in help reduce anxiety in children in the environment House Sick .